The use of medial clavicular epiphysis ossification stages for bone age determination - Win, Nu Nu; Erok, Berrin (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Introduction. Bone age determination is a radiological method investigating the compatibility of ossification processes of bones with chronological ages. Aim. We aimed to investigate the use of CT staging of the medial clavicular epiphyseal ossification in bone age determination in Turkish adolescents and young adults. Material and methods. Chest CT exams of 2018 patients between 11 and 35 years of age were retrospectively evaluated for epiphyseal ossification stages of the bilateral medial clavicles (4036 clavicles) on both axial&coronal images and compared with the sex and chronologic age of the individuals in Turkey. Results. For stage 2,3 and 4 the ages of women were greater than men and it was statistically significant. For an individual classified as stage 4,it can be said with certainty that he or she has already reached the age of 18.There was no statistically significant difference between left&right sides and between the axial&coronal images.In addition, it was found that the medial clavicular head epiphyses showed a lot of variation. Conclusion. CT evaluation of the medial clavicular epiphysis ossification stages is helpful in determination of the individuals over the age of 18. Regardless of the sex, the stage 4 can be used as a criterion to make the prediction that an individual is older than 18 years.
This retrospective study was approved by the local ethics committee of the Istanbul Medical Faculty with the IRB number of 621.
Keywords: bone age; clavicle; medial clavicular epiphysis; skeletal age